Clinical and Immunologic Efficacy of the Recombinant Adenovirus Type-5-Vectored (CanSino Bio) Vaccine in University Professors during the COVID-19 Delta Wave - Santos Guzmán-López; Armine Darwich-Salazar; Paola Bocanegra-Ibarias; Daniel Salas-Treviño; Samantha Flores-Treviño; Eduardo Pérez-Alba; Laura M. Nuzzolo-Shihadeh; Edelmiro Pérez-Rodríguez; Adrián Camacho-Ortiz (Vaccines, 2022)
Information regarding the efficacy of the recombinant adenovirus type-5-vectored (CanSino Bio) vaccine against the COVID-19 disease in a real-life setting is limited. A retrospective cohort study was carried out in the teaching university community of the metropolitan area of Monterrey, Mexico, through a four-section survey, and during the COVID-19 delta wave. Determination of IgG antibodies against SARS-CoV-2 spike (S) protein was performed in a subset of participants vaccinated with CanSino Bio. A total of 7468 teachers responded to the survey, and 6695 of them were fully vaccinated. Of those, 72.7% had CanSino Bio, 10.3% Pfizer, 8.4% AstraZeneca, 1.2% Moderna, and 2.7% others. Symptomatic breakthrough infections were recorded in those vaccinated with CanSino Bio (4.1%), AstraZeneca (2.1%), and Pfizer (2.2%). No difference was found between CanSino Bio and other vaccines regarding hospitalization, the need for mechanical ventilation, and death. For CanSino Bio recipients, anti-S antibodies were >50 AU/mL in 73.2%. In conclusion, primary breakthrough symptomatic infections were higher in the CanSino vaccinated group compared to other brands. Individuals with a previous infection had higher antibody levels than those who were reinfected and without infection. A boosted dose of CanSino is recommended for those individuals without a previous infection.